2010
DOI: 10.1097/ppo.0b013e3181dbebf9
|View full text |Cite
|
Sign up to set email alerts
|

Biological Rationale and Current Clinical Experience With Anti-Insulin-Like Growth Factor 1 Receptor Monoclonal Antibodies in Treating Sarcoma

Abstract: Two decades have elapsed since insulin-like growth factor-1 receptor (IGF-1R) signaling was initially implicated in sarcoma biology to the first clinical experience of IGF-1R blockade in sarcoma. During these 21 years, the IGF pathway and its key mediator IGF-1R have been implicated in the genesis, growth, proliferation, metastasis, and resistance to conventional treatment in several sarcoma subtypes. In addition, IGF-1R has been validated, both in vitro and in vivo, as a target for the treatment of sarcoma. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 109 publications
0
43
0
Order By: Relevance
“…Other emerging molecularly targeted drugs have shown promising results in early trials, such as IGF1-R (Insulin-like Growth Factor-1 Receptor) monoclonal antibodies in Ewing's sarcoma [8].…”
Section: Purposementioning
confidence: 99%
“…Other emerging molecularly targeted drugs have shown promising results in early trials, such as IGF1-R (Insulin-like Growth Factor-1 Receptor) monoclonal antibodies in Ewing's sarcoma [8].…”
Section: Purposementioning
confidence: 99%
“…Expression of IGF ligands and IGF-1R in these tumors has long suggested that the pathway is activated via an autocrine loop. 4,5 Importantly, malignant transformation induced by the pathognomonic ESFT EWS/FL-1 fusion gene (product of t(11;22)) is dependent on IGF-1R. 6 The EWS/FL-1 fusion also promotes IGF-1R activation by repressing the expression of IGFBP-3, a binding protein that negatively regulates IGF-1R signaling by sequestering IGF-1 in the serum.…”
mentioning
confidence: 99%
“…Minimal activity (2.4% ORR and 26% SD in 167 patients) was seen in other STS subtypes [111,112]. Several other IGF-1R monoclonal antibodies are currently being tested in sarcoma patients; these efforts were recently reviewed [113].…”
Section: Insulin-like Growth Factor-1 Receptor (Igf-1r) Inhibitorsmentioning
confidence: 99%